Trends, Technology and Addiction: An Explorative Study on Cyber Behavior of Students - Dash, Devi Prasad; Akhtar, Shamim (Indian Journal of Marketing, 2012)
The Internet has revolutionized every sphere of our life. From the urgency of office cubicles to the comfort of our home recliners, people are living a substantial part of their everyday hours online. And now, with the emergence of portable devices such as smart phones, net-books and tablets, everyone is "connected", even while they are on the move. No doubt, the internet has opened up a whole big window of unlimited possibilities for everyone. From social networking to net-banking, it has, in many ways, made our life simpler, fancier and better. However, on the other hand, it has also caused serious concerns, and at times, has posed threats that tend to go beyond our ordinary control. Today, the students, especially the ones in their teens and early twenties have become the most vulnerable segment to fall on the wrong side of this revolutionary technology. This article explores internet usage behaviour among a selected sample of college and school students from Lunglei town in Mizoram, and on the basis of the findings of the study, it draws suggestions for more healthy and productive use of the Internet.